2015
DOI: 10.1097/njh.0000000000000187
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Rehabilitation and Palliative Care for the Lung Cancer Patient

Abstract: Pulmonary rehabilitation, as a quality of life intervention, has a role to play in palliative care for lung cancer patients. Combining the art and skills of clinical care, physiological, and behavioral tools, pulmonary rehabilitation can serve to rebuild the functional capacity of patients limited by breathlessness and deconditioning. Exercise programs are the primary tool used to restore and rebuild the patient's endurance by challenging the entire pathway of oxygen transport and improving gas exchange. Other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 49 publications
0
12
0
6
Order By: Relevance
“…Dentre os trabalhos analisados, cinco evidenciaram não haver diferença significativa entre os exercícios aeróbicos, resistivos ou mistos na melhora da qualidade de vida, controle de sintomas e melhora do sistema imune 14,15,16,17,18 , porém um estudo comprovou melhora da força muscular no grupo de exercícios resistivos quando comparado ao grupo de exercícios aeróbicos 15 .…”
Section: G2 -Controleunclassified
“…Dentre os trabalhos analisados, cinco evidenciaram não haver diferença significativa entre os exercícios aeróbicos, resistivos ou mistos na melhora da qualidade de vida, controle de sintomas e melhora do sistema imune 14,15,16,17,18 , porém um estudo comprovou melhora da força muscular no grupo de exercícios resistivos quando comparado ao grupo de exercícios aeróbicos 15 .…”
Section: G2 -Controleunclassified
“…Existen herramientas de la rehabilitación pulmonar que incluyen entrenamiento de la respiración, como la respiración con labios fruncidos para mejorar el intercambio gaseoso y disminuir la disnea; habilidades en el automanejo de manera que mejore la confianza y permita un mejor entendimiento de la enfermedad; técnicas de aclaramiento de vías aéreas, optimización de la broncodilatación, cesación de tabaquismo y terapia de oxígeno (16).…”
Section: Rehabilitación Pulmonar Y Cuidados Paliativosunclassified
“…El tratamiento de la disnea tiene varios componentes, ya sea fisiológico, psicológico o una combinación de ambas. A corto plazo se encuentra la meditación, los medicamentos y ejercicios respiratorios; mientras que, a largo plazo, los ejercicios de entrenamiento son altamente efectivos (16).…”
Section: Rehabilitación Pulmonar Y Cuidados Paliativosunclassified
See 1 more Smart Citation
“…Management of dyspnea relies on the immediate treatment of breathlessness with medication and oxygen/air therapy, as well as pulmonary rehabilitation including exercises, breathing retraining, and smoking cessation [ 58 ]. Studies have indicated that a combination of pharmaceutical treatment of underlying causes and longer-term therapies for symptom suppression are the most effective [ 62 ].…”
Section: Palliative Therapiesmentioning
confidence: 99%